2011
DOI: 10.1096/fj.11-184895
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania majorparasite stage‐dependent host cell invasion and immune evasion

Abstract: Leishmania pathogenesis is primarily studied using the disease-inducing promastigote stage of Leishmania major. Despite many efforts, all attempts so far have failed to culture the disease-relevant multiplying amastigote stage of L. major. Here, we established a stably growing axenic L. major amastigote culture system that was characterized genetically, morphologically, and by stage-specific DsRed protein expression. We found parasite stage-specific disease development in resistant C57BL/6 mice. Human neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
1
44
0
1
Order By: Relevance
“…61,62 Apoptotic and viable promastigotes were purified from stationary phase promastigotes by magnetic separation, as described previously. 1 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…61,62 Apoptotic and viable promastigotes were purified from stationary phase promastigotes by magnetic separation, as described previously. 1 …”
Section: Methodsmentioning
confidence: 99%
“…Cells were permeabilized by saponin (Sigma, S7900) and stained with DAPI, a polyclonal rabbit anti-human LC3 Ab (Cell Signaling Technology, 2775S), and an anti-Lm polyclonal Ab obtained from Lm infected Balb/c mice. 62 For detection, chicken antimouse Alexa 488 (A21200) and goat anti-rabbit Alexa Fluor 568 (A11036) were used (Molecular Probes/Invitrogen). Chamber slides were analyzed using a Zeiss Observer, Zeiss LSM7 Live and Axiovision/ZEN 2009 Software (Carl Zeiss, G€ ottingen, Germany).…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the newly described method for culturing axenic L. major amastigotes yields parasites that are not readily internalized by human neutrophils (60). Additionally, it has been shown that L. donovani amastigotes derived from infected hamsters are degraded by human neutrophils (24).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we recently reported that Syt XI, which inhibits vesicle fusion (38), dampens the secretion of both TNF and IL-6 (26). Interestingly, it has been demonstrated that L. major promastigotes induce the secretion of TNF and IL-6 following their internalization by macrophages (9,(39)(40)(41)(42). This raises the possibility that these parasites could disrupt membrane fusion regulators to induce proinflammatory cytokine release.…”
mentioning
confidence: 99%